Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12094-016-1522-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose intensification in pre-operative chemo-radiotherapy for locally advanced rectal cancer

Abstract: Preliminary results did not confirm some advantages in terms of primary tumor downstaging/downsizing compared to conventional schedules reported in historical series. The role of 18-FDG-PET/CT in neoadjuvant rectal cancer management needs to be confirmed in further investigations. Long terms results are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…magnetic resonance imaging, MRI) and even more on metabolic imaging suitable for predicting CRT response is constantly increasing [ 8 , 9 ]. In this regard, the role that [18F] -fluorodeoxyglucose positron emission tomography/computed tomography ([18F] FDG-PET/CT) has in staging and treatment planning of rectal cancer is still quite debatable [ 10 12 ] as well as in measuring treatment response [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…magnetic resonance imaging, MRI) and even more on metabolic imaging suitable for predicting CRT response is constantly increasing [ 8 , 9 ]. In this regard, the role that [18F] -fluorodeoxyglucose positron emission tomography/computed tomography ([18F] FDG-PET/CT) has in staging and treatment planning of rectal cancer is still quite debatable [ 10 12 ] as well as in measuring treatment response [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 78% of patients completed the prescription dose (59.4 Gy in 33 fractions or 60 Gy in 30 fractions) of radiotherapy, the average radiation dose was 56.69 Gy, and the average BED was 67 Gy. Previous studies showed that a prescription dose of 54 Gy to 60 Gy (BED = 65 to 72 Gy) delivered to rectal tumors would achieve a significant tumor regression effect, and the percentage of patients with tumor regression grade (TRG) 1 and 2 was approximately 60 to 63.9% [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Here the V40 of the lumbosacral spine was associated with clinically significant grade ≥ 2 hematologic toxicity in patients receiving conventional concurrent CRT (50 à 2 Gy, IMRT, Capecitabine) (grade ≥ 2hematologic toxicity with V40 ≥ 60% vs. V40 < 60% was 38.3% vs.13%, p = 0.005). Interestingly, no case of severe acute toxicity was registered in a radiation dose intensification study in rectal cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%